C.12 - Laski, Harold (New Delhi, 1986)
This is a little book to remove painlessly some of the passion, prejudice and ignorance that cloud political discussion ; a book to deepen the general reader's understanding of what politics is really about. Hoiding the past and the present, and the ideal and the real, in just balance, Professor Laski examines the nature of the state and its organisation, how it meets the needs of those composing it, and how it is being forced more and more inevitably into a wider whole:a world government. Never was it more necessary that these principles, fundamental to human organisation all over the world, should be universally understood.
Keywords: Political science